Electrotextile-Based Flexible Electromagnetic Skin for Wearables and Remote Monitoring - Rossella Rizzo; Giuseppe Ruello; R. Massa; Maxim Zhadobov; Giulia Sacco (IEEE Journal of Microwaves)
This paper presents a flexible electrotextile-based solid skin-equivalent phantom operating in the millimeter-wave (mmW) range. The phantom reproduces the reflection coefficient at the air/skin interface in the 55–65 GHz band. It is composed of a layer of carbon powder mixed with silicone and backed with an electrotextile. Its thickness is optimized to approach the target reflection coefficient of the human skin. For the angles of incidence from $0 ^{°}$ to $60 ^{°}$ the maximum relative error in respect to the target value is $2.6%$ for the magnitude and $13%$ for the phase when considering impinging transverse electric (TE) and transverse magnetic (TM) polarized plane wave. To experimentally validate the phantom, its scattering properties are measured in the 55–65 GHz range using a free-space transmission/reflection system. A good agreement between the numerical and experimental results is demonstrated, exhibiting a relative error within $1.9 %$ for the magnitude of the reflection coefficient in the 55–65 GHz range at normal incidence. Such phantoms may be used in a wide range of body-centric mmW applications, including remote sensing and medical applications.